2012
DOI: 10.2190/ns.22.3.e
|View full text |Cite
|
Sign up to set email alerts
|

From Agricultural Fields to Urban Asphalt: The Role of Worker Education to Promote California's Heat Illness Prevention Standard

Abstract: This article describes an innovative approach to reach and educate workers and worker advocates about California's outdoor heat illness prevention standard. In 2010, Cal/OSHA initiated a statewide education campaign to reduce heat-related illnesses and fatalities and increase awareness of the standard's requirements. In Southern California, the UCLA Labor Occupational Safety and Health Program (LOSH) focused on three principal strategies of community-based outreach, popular education, and organizational capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Finally, there is an inherent ambiguity in the AMHP2012. The stated goal is to prevent employers from exposing workers to health-impairing heat, but if the HTS cost is not large enough, as revealed in most cases under the fixed standard, the employers may prefer to pay the subsidy rather than reducing the working time (35). Weak costs could have additional perverse effects, such as encouraging work in potentially dangerous conditions or conversely, discouraging employers from investment into costly protecting measures, like air conditioning, for indoor workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is an inherent ambiguity in the AMHP2012. The stated goal is to prevent employers from exposing workers to health-impairing heat, but if the HTS cost is not large enough, as revealed in most cases under the fixed standard, the employers may prefer to pay the subsidy rather than reducing the working time (35). Weak costs could have additional perverse effects, such as encouraging work in potentially dangerous conditions or conversely, discouraging employers from investment into costly protecting measures, like air conditioning, for indoor workers.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility calls for complementary strategies to protect the workers while limiting escalation of heat-related working costs. The recent enforcement of mandatory heat standards in two states in the United States, California and Washington, which do not include any HTS but focus on education and training (35)(36)(37), may offer lessons to guide a more effective implementation of the Chinese heat stress prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that about half of respondents were not satisfied with current heat prevention measures, reflecting the necessity to upgrade current heat policies and strategies. Australia has mandatory heat regulations in place to protect workers from extreme heat; however, at present there are many ambiguities which may hinder implementation and effectiveness [ 4 , 36 ]. According to the survey results, provision of cool drinking water was the most common heat prevention measure, which is also required by the national Model Code of Practice (managing the work environment and facilities) [ 37 ]; however, this is not available in all Australian workplaces according to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…the Construction, Forestry, Mining and Energy Union (CFMEU) [ 39 ]) have made specific heat stress management guidelines. Nevertheless, the unenforceable and non-mandatory nature of the guidelines may raise the problem of low compliance [ 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation